The Effect of Tuja Shuttle Run Training on Changes in Body Weight, Body Mass Index (BMI), Speed, VO?max, and Agility in Sepak Takraw Athletes - Aprillia Raisha Zahra, Tutur Jatmiko, Kunjung Ashadi, Donny Ardi Kusuma, Bülent Agbuga, Maryam Abdul (Lembaga Bale Literasi, 2025)
This study aims to analyze the effect of Tuja Shuttle Run training on changes in body weight, Body Mass Index (BMI), speed, VO?max, and agility in sepak takraw athletes. The study uses a quantitative approach with a quasi-experimental design through a one-group pre-test and post-test design. The research subjects consisted of 13 female sepak takraw athletes from Magetan Regency aged 13–16 years who were preparing to participate in the 2025 East Java Provincial Sports Week (Porprov). The training program consisted of Tuja Shuttle Run High-Intensity Interval Training (HIIT) for 6 weeks, three times a week, consisting of 5 sets and 3 repetitions with a work-to-rest ratio of 1:5 at an intensity of 85–95% HRmax. Measurements included body weight and BMI, speed using a 20-meter sprint, VO?max using the Multistage Fitness Test (MFT), and agility using the T-Test. Data analysis was performed using the Shapiro–Wilk normality test, followed by a paired sample t-test at a significance level of 0.05. The results showed significant differences in BMI (p=0.020), speed (p=0.000), VO?max (p=0.000), and agility (p=0.000) between the pre-test and post-test results. These findings indicate that high-intensity interval training using the Tuja Shuttle Run model is effective in improving physical biomotor components and supporting changes in the body composition of sepak takraw athletes.